Inhibition of Cathepsin S Induces Mitochondrial Apoptosis in Glioblastoma Cell Lines Through Mitochondrial Stress and Autophagosome Accumulation - Fei, Maoxing; Zhang, Li; Wang, Handong; Zhu, Yihao; Niu, Wenhao; Tang, Ting; Han, Yanling (Frontiers in Oncology, 2020)
Cathepsin S (CTSS), a lysosomal cysteine protease, is overexpressed in various cancers, including glioblastoma (GB). A high level of CTSS is associated with tumor progression and poor outcome in GB. However, the underlying mechanisms of its role in the biological characteristics of GB remain to be elucidated. Here, we uncovered a potential role of CTSS in the lysosomes and mitochondria of GB cells (GBCs). Downregulation of CTSS in GBCs could increase the expression of autophagy-related proteins; however, there was no significant change in p62, suggesting autophagy blockade. Moreover, inhibition of CTSS increased the expression of mitochondrial calcium uniporter (MCU) and enhanced mitochondrial Ca2+ uptake ability, causing mitochondrial Ca2+ overload, the generation of copious reactive oxygen species (ROS) and eventual mitochondrial apoptosis. Additionally, elevated damage to mitochondria exacerbated the burden of autophagy. Finally, we found that silence of MCU could alleviate the inhibition of CTSS-induced autophagosome accumulation and mitochondrial stress. Collectively, these results demonstrate that CTSS plays an important role in the process of autophagic flux and mitochondrial functions in GBCs.